The Difference in Long Jump Achievement and Academic Achievement of Grade VIII Students Based on the Mode of Transportation to School at SMP Negeri 4 Sleman - Dheiryx Nanda Karambe; Hedi Ardiyanto Hermawan (International Journal of Health and Medicine, 2026)
Background: Daily physical activity is one of the factors that play a role in maintaining the physical fitness of students. One form of physical activity that is carried out every day is the use of active modes of transportation to school, such as walking and cycling. This study aims to determine the difference between long jump achievement and academic achievement of grade VIII students based on the mode of transportation used, namely motorcycles, bicycles, and walking. This study uses a quantitative approach with a comparative research design. The research sample amounted to 112 students in grade VIII of SMP Negeri 4 Sleman who were selected using the purposive sampling technique. The independent variable in this study was the mode of transportation to school, while the bound variable included long jump achievement and academic achievement. Data was collected through long jump practice tests, documentation of report cards, and questionnaires about the mode of transportation used by students. Data analysis was carried out using descriptive statistics, normality test, homogeneity test, Kruskal-Wallis test, and continued with the Mann-Whitney test. The results showed that there was a significant difference in the achievement of long jump based on the mode of transportation used by the students (p < 0.05). Students who use bicycles get much better jump results than students who walk or use motorcycles. Conversely, no significant differences were found in academic achievement based on the mode of transportation used (p > 0.05). The findings of the study show that the use of active modes of transportation is related to students' physical abilities, but has not shown a relationship with academic achievement. The results of this research can be the basis for schools to encourage the use of active transportation as part of efforts to improve the physical fitness of students.